Morphological and Molecular Characterization of a New Trichuris Species (Nematoda- Trichuridae), and Phylogenetic Relationships of Trichuris Species of Cricetid Rodents from Argentina - Robles, Maria del Rosario (2014)
Populations of Trichuris spp. isolated from six species of sigmodontine rodents from Argentina were analyzed based on morphological characteristics and ITS2 (rDNA) region sequences. Molecular data provided an opportunity to discuss the phylogenetic relationships among the Trichuris spp. from Noth and South America (mainly from Argentina). Trichuris specimens were identified morphologically as Trichuris pardinasi, T. navonae, Trichuris sp. and Trichuris new species, described in this paper. Sequences analyzed by Maximum Parsimony, Maximum Likelihood and Bayesian inference methods showed four main clades corresponding with the four different species regardless of geographical origin and host species. These four species from sigmodontine rodents clustered together and separated from Trichuris species isolated from murine and arvicoline rodents (outgroup). Different genetic lineages observed among Trichuris species from sigmodontine rodents which supported the proposal of a new species. Moreover, host distribution showed correspondence with the different tribes within the subfamily Sigmodontinae.